Viability Study of Machine Learning-Based Prediction of COVID-19 Pandemic Impact in Obsessive-Compulsive Disorder Patients - Tubío-Fungueiriño, María; Cernadas, Eva; Gonçalves, Óscar F.; Segalas, Cinto; Bertolín, Sara; Mar-Barrutia, Lorea; Real, Eva; Fernández-Delgado, Manuel; Menchón, Jose M.; Carvalho, Sandra; Alonso, Pino; Carracedo, Angel; et al. (Frontiers in Neuroinformatics, 2022)
Background: Machine learning modelling can provide valuable support in different areas of mental health, because it enables to make rapid predictions and therefore support the decision making, based on valuable data. However, few studies have applied this method to predict symptoms’ worsening, based on sociodemographic, contextual, and clinical data. Thus, we applied machine learning techniques to identify predictors of symptomatologic changes in a Spanish cohort of OCD patients during the initial phase of the COVID-19 pandemic. Method: 127 OCD patients were assessed using the Yale–Brown Obsessive-Compulsive Scale (Y-BOCS) and a structured clinical interview during the COVID-19 pandemic. Machine learning models for classification (LDA and SVM) and regression (linear regression and SVR) were constructed to predict each symptom based on patient's sociodemographic, clinical and contextual information. Results: A Y-BOCS score prediction model was generated with 100% reliability at a score threshold of ±6. Reliability of 100% was reached for obsessions and/or compulsions related to COVID-19. Symptoms of anxiety and depression were predicted with less reliability (correlation R of 0.58 and 0.68, respectively). The suicidal thoughts are predicted with a sensibility of 79% and specificity of 88%. The best results are achieved by SVM and SVR. Conclusions: Our findings reveal that sociodemographic and clinical data can be used to predict changes in OCD symptomatology. Machine learning may be valuable tool for helping clinicians to rapidly identify patients at higher risk and therefore provide optimized care, especially in future pandemics. However, further validation of these models is required to ensure greater reliability of the algorithms for clinical implementation to specific objectives of interest.